STRATEGI GURU PENDIDIKAN AGAMA ISLAM MEMOTIVASI SISWA MENGERJAKAN TUGAS DI SMA N 1 AMPEK NAGARI - Yulyana; Junaidi Junaidi; Charles Charles; Supratman Zakir (KOLONI, 2022)
The background of this research is related to some students who are less than optimal in doing the tasks given, and during the learning process there are some students who are not active in the learning process. Students are less motivated in learning and making assignments because Islamic Religious Education teachers very rarely use strategies that can generate student learning motivation. One of them is seen from the number of students who are bored in getting the material presented from educators because educators are very monotonous when delivering the material. In addition, the use of learning strategies that are less as a result, students easily feel bored and their achievement in learning decreases. The atmosphere in learning has not been conditioned when the teacher gives assignments, this is something that every educator must pay attention to. How to use learning strategies that please students, so that their interest in learning is getting better and they are able to know the material presented by the teacher. Therefore, the creativity of an educator in teaching is needed in students. This research is located in SMA N 1 Ampek Nagari, Agam district with the object of the problem, namely the Strategy of Islamic Religious Education Teachers Motivating Students to Do Assignments at SMA N 1 Ampek Nagari. This type of research is descriptive qualitative research, in collecting data the researchers used interview, observation and documentation techniques. Meanwhile, to analyze it, the researcher used steps of data reduction, data presentation and drawing conclusions. From the research that has been done, it can be concluded that the teacher's strategy to increase student motivation in doing assignments at SMA N 1 Ampek Nagari has been going quite well according to the target, the strategy given by the teacher with the method and way of delivering it. Such as by giving praise, appreciation, and motivation that can build students. By using lecture and discussion methods that can lead students to be more active and develop their ability to dare to speak. Keywords: PAI Teacher Strategy, Motivating Students to Do Assignments